IDENTIFIYING STUDY ON FACTOR THAT INFLUENCE STUDENTS’ ACTIVENESS IN MATHEMATICS LEARNING DESIGN SUBJECT - Sukma Mawaddah; Lalu Muchsin Effendi; Irzani . (Jurnal Pendidik Indonesia (JPIn), 2018)
Mathematics Education Department student as future teacher must be active in learning process, especially to improve their pedagogic competence, one of these competencies is to plan Mathematics learning design. The purpose of this research is to identify and to describe the factors that cause student for being active in Mathematics learning process, on Mathematics learning Design subject in Mathematics Education Program, Education and Teacher Training Faculty, Islamic State University of Mataram, 2016/2017 academic year. This research is qualitative type of descriptive study case. Using purposive sampling technic with Milles and Hubberman models’ data analyzed. There are data reduction, data display, and verification. The result of this research is the factors that influenced student learning activeness are: (a) internal factors of student, (b) external factors of student, (c) learning approach of students own, and (d) learning goals.